Labor Turnover, Job-Specific Skills, and Efficiency in a Search Model - Deere, Donald R. (Quarterly Journal of Economics, 1987)
This paper analyzes the implications for turnover of costly job-specific training. The presence of such costs in a search model implies that turnover decisions reduce the value of potential trades that are available to other market participants. There is too much turnover because of this external effect, and, therefore, too much retraining. When the investment in job training is endogenous, inefficient turnover again occurs, and the investment in specific skills is inefficiently high. The interactions between skill acquisition and turnover imply that it is essentially impossible for a brokerage institution to achieve efficiency.